(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2019)
The deployment of Information Communication Technology in the Road sector has contributed positively towards achieving the national goal of ICT for infrastructure development. However, the deployment of ICT software for Road infrastructure in underdeveloped countries has been done with duplication of efforts contributing to software failure. This study aimed in evaluating the effectiveness and economic values of the Road Maintenance Management System in Tanzania. The study deployed System Usability Scale Framework in 26 regions of Tanzania, and Kruskal-Wallis test was used for significance testing. The result indicates positive response of adopting and scaling the Road Maintenance Management System to all 26 regions in the country with R2=0.863. The usability of the system remains steady for almost three years from 2017 to 2019. The economic value of system is found to be above average (61%), while the value for money is found to reach 76.5% of the expectation. It is therefore concluded that the use of ICT in planning for Roads Maintenance increases efficiency in delivery critical factors that facilitated decision making in road planning and also improves specific services delivery in government efficiency.